Inhalation of Rose Aromatherapy Against Anxiety of Heart Patients - Yeli Yulianti; Sidik Awaludin (Eduvest - Journal of Universal Studies, 2024)
Cardiovascular disease remains a serious global threat and the leading cause of death worldwide. Patients with heart problems face significant physical and emotional challenges. This article uses a systematic design review concerning PRISMA to investigate the effect of rose aromatherapy inhalation on anxiety of heart patients. Data were synthesized from the Quasy Experiment and RCT by formulating PICO (Heart patients, Rose aromatherapy inhalation, Control group, Decreased anxiety levels). The results of the analysis of the six articles showed that rose aromatherapy had a positive influence on reducing anxiety in heart patients. Despite variations in research methods, these results overall support the potential effectiveness of rose aromatherapy as an additional approach to relieve anxiety in heart patients.